Design of a Body with Depth Control System for an Underwater Glider - Ghani, Muhamad Fadli; Abdullah, Shahrum Shah (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2014)
The underwater glider is used for deep water to observe large areas with minimal use of energy and move through the water by changing the body weight. The glider contained a cylindrical body attached with two wings and a fix tail. The controller has been designed to use a comparator circuit integrate with a pressure sensor to control the depth level. The pressure sensor mounted on the glider used to sense the underwater pressure. For the beginning, this underwater glider is limited to a depth of 0-10 meters.